(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Topic. The article is dedicated to the analysis of issues and prospects of the banking system in Uzbekistan, exploring key aspects of its current state and identifying challenges it faces. Security issues in the banking system are also addressed. Purpose. The aim of this abstract is to examine a range of problems in the banking sector of Uzbekistan and identify possible solutions. The analysis includes the significance of regulation, financial risks, and technological challenges, along with proposing strategies to ensure stability and development of the banking system. Methodology. The research is based on the analysis of current data on the banking system of Uzbekistan, including financial reports, reports from regulatory bodies, and international assessments. Interview and abstraction methods are applied to identify key problems and prospects. Results. The analysis has identified several key problems, including bureaucracy, corruption, and a lag in digitization. Concrete measures are proposed for improving regulation and supervision, risk management, and innovation implementation, which can contribute to the stability of the banking system. Conclusions. In conclusion, it is emphasized that addressing the identified problems requires a comprehensive approach, including balanced regulation, development of financial instruments, and innovative updates. Paths for collaboration with the government, active implementation of digital technologies, and a change in banking culture are suggested to achieve a sustainable and adaptive banking system in Uzbekistan.